An exploration of crimes related to online dating - Davis, Megan (2018)
This thesis explores crimes related to online dating. After an introduction to online dating crimes (chapter 1), a systematic literature review (chapter 2) looks at current studies considering online dating romance scams. Studies indicate several factors that make victims more vulnerable to these scams, such as their romantic beliefs. Techniques used by scammers are also discussed. Chapter 2 collates what is known so far and highlights gaps in the literature: namely the lack of research.